Exploring the invasion of rangelands by Acacia mearnsii (black wattle): biophysical characteristics and management implications. Issue 4 (1st October 2016) - Gwate, Onalenna; Mantel, Sukhmani K; Finca, Andiswa; Gibson, Lesley A; Munch, Zahn; Palmer, Anthony R
Abstract : Australian acacias have spread to many parts of the world. In South Africa, species such as A. mearnsii and dealbata are invasive. Consequently, more effort has focused on their clearing. In a context of increasing clearing costs, it is crucial to develop innovative ways of managing invasions. Our aim was to understand the biophysical properties of A. mearnsii in grasslands as they relate to grass production and to explore management implications. Aboveground biomass (AGB) of A. mearnsii was determined using a published allometric equation in invaded grasslands of the northern Eastern Cape, South Africa. The relationships among the A. mearnsii leaf area index (LAI), normalised difference vegetation index (NDVI) and AGB were investigated. The influence of A. mearnsii LAI and terrain slope on grass cover was also investigated. Strong linear relationships between NDVI, LAI and AGB were developed. Acacia mearnsii canopy adversely impacted grass production more than terrain slope ( p < 0.05) and when LAI approached 2.1, grass cover dropped to below 10% in infested areas. Reducing A. mearnsii canopy could promote grass production while encouraging carbon sequestration. Given the high AGB and clearing costs, it may be prudent to adopt the 'novel ecosystems' approach in managing infested landscapes.